2016
DOI: 10.1073/pnas.1613187113
|View full text |Cite
|
Sign up to set email alerts
|

Key role for neutrophils in radiation-induced antitumor immune responses: Potentiation with G-CSF

Abstract: Radiation therapy (RT), a major modality for treating localized tumors, can induce tumor regression outside the radiation field through an abscopal effect that is thought to involve the immune system. Our studies were designed to understand the early immunological effects of RT in the tumor microenvironment using several syngeneic mouse tumor models. We observed that RT induced sterile inflammation with a rapid and transient infiltration of CD11b + Gr-1 high+ neutrophils into the tumors. RT-recruited tumor-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 51 publications
10
139
0
Order By: Relevance
“…Neutrophil recruitment by dying tumor cells has been described recently in a mouse model where culture supernatants of tunicamycin- or mitoxanthrone-treated tumor cells were injected into the ear pinnae and in different mouse flank tumors irradiated with high single doses of 15 Gy, 48,49 thus confirming our air pouch findings. The authors of both studies also observed an essential contribution of CXCL1 together with CCL2, CXCL10, and G-CSF.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Neutrophil recruitment by dying tumor cells has been described recently in a mouse model where culture supernatants of tunicamycin- or mitoxanthrone-treated tumor cells were injected into the ear pinnae and in different mouse flank tumors irradiated with high single doses of 15 Gy, 48,49 thus confirming our air pouch findings. The authors of both studies also observed an essential contribution of CXCL1 together with CCL2, CXCL10, and G-CSF.…”
Section: Discussionsupporting
confidence: 89%
“…Yet, evidence is available that neutrophils can engulf dying tumor cells, exert cytotoxic activity against residual, therapy-surviving tumor cells, and thus can contribute to therapy-induced tumor control. 48,49 Additionally, neutrophils are able to create a favorable chemokine milieu for the invasion of monocytic cells and tumor-specific cytotoxic T cells. 45,49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, depleting CD8 + T cells or interrupting the STING pathway in DC resulted in therapeutic failure . Radiotherapy can also induce sterile inflammation in the TME, indicated by a rapid and transient infiltration of neutrophils, which may be capable of eliminating tumors by releasing ROS …”
Section: Immune‐modulatory Properties Of Cancer Therapiesmentioning
confidence: 99%
“…70 Radiotherapy can also induce sterile inflammation in the TME, indicated by a rapid and transient infiltration of neutrophils, which may be capable of eliminating tumors by releasing ROS. 71 Focal tumor ablation with HIFU, PDT, cryoablation, or radiofrequency ablation can also elicit long-term control of malignancies by boosting systemic immune reactions. These strategies rapidly shrink tumors by causing physical stresses or ROS-mediated damage.…”
Section: Immune-dependent Tumor Eradicationmentioning
confidence: 99%